Near-Infrared Fluorescence Imaging of Breast Cancer and Axillary Lymph Nodes After Intravenous Injection of Free Indocyanine Green - Bourgeois, Pierre; Veys, Isabelle; Noterman, Danielle; De Neubourg, Filip; Chintinne, Marie; Vankerckhove, Sophie; Nogaret, Jean-Marie (Frontiers in Oncology, 2021)
Background Near-infrared fluorescence imaging (NIRFI) of breast cancer (BC) after the intravenous (IV) injection of free indocyanine green (fICG) has been reported to be feasible. However, some questions remained unclarified. Objective To evaluate the distribution of fICG in BC and the axillary lymph nodes (LNs) of women undergoing surgery with complete axillary LN dissection (CALND) and/or selective lymphadenectomy (SLN) of sentinel LNs (NCT no. 01993576 and NCT no. 02027818). Methods An intravenous injection of fICG (0.25 mg/kg) was administered to one series of 20 women undergoing treatment with mastectomy, the day before surgery in 5 (group 1) and immediately before surgery in 15 (group 2: tumor localization, 25; and pN+ CALND, 4) as well as to another series of 20 women undergoing treatment with tumorectomy (group 3). A dedicated NIR camera was used for ex vivo fluorescence imaging of the 45 BC lesions and the LNs. Results In group 1, two of the four BC lesions and one large pN+ LN exhibited fluorescence. In contrast, 24 of the 25 tumors in group 2 and all of the tumors in group 3 were fluorescent. The sentinel LNs were all fluorescent, as well as some of the LNs in all CALND specimens. Metastatic cells were found in the fluorescent LNs of the pN+ cases. Fluorescent BC lesions could be identified ex vivo on the surface of the lumpectomy specimen in 14 of 19 cases. Conclusions When fICG is injected intravenously just before surgery, BC can be detected using NIRFI with high sensitivity, with metastatic axillary LNs also showing fluorescence. Such a technical approach seems promising in the management of BC and merits further investigation.